Reciprocal Teaching as a Strategy to Improve Students' Understanding of Reading Content (Reading Skill) - Neny Novridewi; Sri Wachyunni; Urip Sulistiyo (Universitas Batanghari Jambi, 2023)
This study aims to improve student's reading skills in class. It was reading skills through the application of the Reciprocal Teaching Strategy. Creating Reciprocal Teaching teaching activities in Reading helps create more profound and meaningful learning. The students were very enthusiastic about understanding the text because they cooperated in groups to summarize and discuss the contents of the text. Each group member has an equal opportunity to read, summarize, discuss, and ask questions. They become more active and show more interest in the lesson. There was an atmosphere of fun and enthusiasm in the class. The results showed that the class was dynamic and lively, so students' learning motivation increased. In addition, student achievement also increased significantly.